The Important Role of Parents for Children in the Negative Impact of Gadgets - Naila Hanifah Handoko (Journal of Social Science, 2024)
This research aims to find out how parents overcome their feelings of dependence and addiction to gadget technology in elementary school children. This research uses a qualitative approach that uses sentences. Interview techniques were used to obtain information about how parents prevent addiction and dependence in children aged 7-9 years on gadgets and were carried out on 18 and 20 June 2024 located in South Manggarai, Tebet sub-district, South Jakarta district, capital city of DKI Jakarta . The participants interviewed were a child from grade 2 to grade 3 and his mother. The research instrument used is a human instrument (own research). The tools used were paper and writing utensils to record information from participants. Technological media in the form of cellphones to record interview results. The analysis technique for this research is a descriptive analytical technique. The results of the research are that there are 3 things parents can do to prevent the negative impact of gadgets. Here's how: (1) managing children's time using gadgets; (2) Do not introduce social media to children; and (3) Scolding is not a fast way to educate children.